2017
DOI: 10.29252/ijree.2.4.66
|View full text |Cite
|
Sign up to set email alerts
|

English Speaking Anxiety: A Study of the Effect of Gender on Iranian EFL University Students’ Perceptions

Abstract: The aim of this study was to examine Iranian EFL university students' level of anxiety and their perceptions towards in-class activities during speaking courses and possible causes of apprehension. Moreover, this study investigated whether or not EFL university students' gender differences affect their perceptions of foreign language speaking anxiety. To this end, data were collected from 175 Iranian EFL learners; 125 females and 50 males through Foreign Language Classroom Anxiety Scale (FLCAS) adopted from Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 13 publications
8
27
1
1
Order By: Relevance
“…The result shows that students in Jagobiao National High School are sometimes experiencing anxiety in oral recitation. This result is in line with the findings of Mohtasham and Farnia (2017) who found out that the students' anxiety has an effect on the performance in school of the students. Lian and Budin (2014) also found out that the students are moderately anxious in terms of English language.…”
Section: Journal Of Social Science Studiessupporting
confidence: 92%
“…The result shows that students in Jagobiao National High School are sometimes experiencing anxiety in oral recitation. This result is in line with the findings of Mohtasham and Farnia (2017) who found out that the students' anxiety has an effect on the performance in school of the students. Lian and Budin (2014) also found out that the students are moderately anxious in terms of English language.…”
Section: Journal Of Social Science Studiessupporting
confidence: 92%
“…As a consequence, the form of anxiety is Mixed Anxiety (MA). Aside from Fajkowska, M., et al which identified these symptoms, Mestan (2017); Mohtasham & Farnia (2017); Anandari (2015); Januariza & Hendriani (2016), noticed signs of anxiety while speaking class that "fear" of making an error was among the roots of the problem. Hence, although the media is beyond of student's ability in the listening section, though it is still quite a matter to engage the easiness of the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…A study at Turkish High School conducted by Mestan (2017) revealed that oral anxiety stems from negative emotions and fear of making mistakes in oral assessment class. Moreover, according to Mohtasham & Farnia (2017) oral English anxiety is caused by concerning to grammar or pronunciation mistakes, insufficient framework consciousness, and worry of missing appearance forward the class. In line with this, most of them appear in oral classes and the most anxiety-causing cause is the feeling fear of making mistakes (Januariza & Hendriani, 2016), feeling uncomfortable, fear until shame (Anandari, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the result of the study shows that anxiety increase in EFL learners when speaking with native speakers. Mohtasham and Farnia (2017) have claimed in their research that students feel anxiety when they speak in front of classmates and teacher and When they an important speech they feel uncomfortable.…”
Section: Literature Reviewmentioning
confidence: 99%